2010
DOI: 10.1093/cid/ciq104
|View full text |Cite
|
Sign up to set email alerts
|

Humoral Response to the Influenza A H1N1/09 Monovalent AS03-Adjuvanted Vaccine in Immunocompromised Patients

Abstract: Influenza A H1N1/09 vaccine elicited a similar antibody response in HIV-infected individuals and in control subjects, whereas SOT recipients had an overall lower response. A second dose of the vaccine only moderately improved vaccine immunogenicity in HIV-infected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
93
2
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(102 citation statements)
references
References 24 publications
6
93
2
1
Order By: Relevance
“…This is most likely due to a high number of patients having detectable antibodies pre-vaccination, reflecting previous use of influenza vaccine in our patient cohort [30,34,35]. After taking into consideration the pre-vaccination titers [28], seroconversion rates increased up to 32-38% for influenza A strains, a rate near of the 40% seroconversion rate which is considered as appropriate for the general population [9,36].…”
Section: Discussionmentioning
confidence: 84%
“…This is most likely due to a high number of patients having detectable antibodies pre-vaccination, reflecting previous use of influenza vaccine in our patient cohort [30,34,35]. After taking into consideration the pre-vaccination titers [28], seroconversion rates increased up to 32-38% for influenza A strains, a rate near of the 40% seroconversion rate which is considered as appropriate for the general population [9,36].…”
Section: Discussionmentioning
confidence: 84%
“…Similar results were shown in other studies, as a single shot of pandemic vaccination in successfully HAART-treated HIV-infected adults generated an antibody response within 21 days, with rates comparable to healthy adults. 22,23 In contrast, other work has suggested a lower response in HIV-infected individuals, even in successfully treated patients. [18][19][20] It may be speculated that the apparent discrepancy is mainly attributable to the baseline level of reactivity to influenza virus antigen that is clearly higher in the HIV group.…”
Section: Discussionmentioning
confidence: 94%
“…21 In contrast, other studies reported a good antibody response in successfully HAART-treated HIV patients. 22,23 However, all these studies addressed the humoral response only, and no information about the ability of pandemic vaccine to elicit a strain-specific and cross-reactive T cell response is available in HIV-infected individuals.…”
Section: Introductionmentioning
confidence: 99%
“…[267,268] These findings of reduced immunogenicity extend to adjuvanted vaccines (AS03 and MF-59) among HIV-positive compared to HIV-negative individuals. [269][270][271] Two systematic reviews conducted on the effectiveness of influenza vaccines among HIV-positive populations showed limited evidence of VE in this population and called for more data from RCT settings. [12,13] However, a recent RCT of TIV among HIV-infected adults in South Africa showed a vaccine efficacy of 76% and high levels of serological conversion.…”
Section: Disease Burdenmentioning
confidence: 99%